Method for accelerating the calculations of exponent on Galois fields by combining parallel processing and pre-calculations - Kozachek, M.S.; Verba, O.A.; Hutsuliak, N.A. (Problems of Informatization and Management, 2025)
Method for exponent calculation on a Galois Field has been developed and researched, with its parallel implementation on an h-core terminal microcontroller for cryptographic applications. The acceleration was achieved due to the following factors: distribution of calculations between h-cores, fast exponentiation to the power of 2k, and simultaneous processing of k digits of the exponent code through the complex use of precomputations. A mathematical proof of the proposed method is given, as well as procedure its operation whose are illustrated be numerical examples. It has been theoretically proven and experimentally confirmed that on a four-core processor and a fragment size of twenty bits, a 20.34-fold acceleration is achieved compared to the classical method of exponentiation on finite Galois fields.